RELATIONSHIP OF HEALTH PROMOTION WITH THE UBERCULOSIS DISEASE AT BASUKI RAHMAT PUBLIC HEALTH CENTER BENGKULU CITY - Yenni Fusfitasari Yenni Fusfitasari (Jurnal Vokasi Keperawatan (JVK), 2020)
The discovery of TB patients is done passively with active promotion. Screening of suspect patients is carried out in health care units supported by active counseling, both by health workers and the community to increase the coverage of TB suspect suspect discovery. The problem in this study is the increased incidence of pulmonary TB disease. The purpose of this research is to know the relationship between health promotion and tuberculosis in Basuki Rahmat Public Health Center Bengkulu City. This type of research is cross sectional study. The population was 19,220 people and the study sample was 99 people. The type of data used in research is to use primary and secondary data. Data analysis in this study used univariate and bivariate data analysis with the statistical method of chi square test at a significance level of 0.05. The results of this study were the majority of respondents (55.6%) who lacked health promotion at the Basuki Rahmat Public Health Center in Bengkulu City. Nearly some respondents (46.5%) who experienced tuberculosis at the Basuki Rahmat Public Health Center in Bengkulu City. There is a relationship between health promotion and tuberculosis in Basuki Rahmat Public Health Center Bengkulu City. For Basuki Rahmat Community Health Center staff, it is necessary to carry out regular monitoring and evaluation and to visit the homes of patients with pulmonary TB in order to improve the knowledge and attitudes of patients with pulmonary TB so that it is expected that patient compliance in pulmonary TB increases.